2020
DOI: 10.1124/dmd.120.000114
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Cytochrome P450 2J3/10 CRISPR/Cas9 Knockout Rat Model

Abstract: Cytochrome P450 2J2 (CYP2J2) enzyme attracts more attention because it not only metabolizes clinical drugs, but also mediates the biotransformation of important endogenous substances and the regulation of physiological function. Although CYP2J2 is very important, few animal models are available to study its function in vivo. In particular, CYP2J gene knockout (KO) rat model for drug metabolism and pharmacokinetics is not available. In this report, the CRISPR/Cas9 technology was used to delete rat CYP2J3/10, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…For example, CYP2J2 transgenic mice have a reduced rate of arrhythmia induction (Westphal et al, 2013). Our previous study also found that knockout of CYP2J3/ 10 in rats led to heart disease (Lu et al, 2020). In addition, CYP2J2*7 allele has been reported to be associated with stroke and CVD (Wang SY.…”
Section: Discussionmentioning
confidence: 92%
“…For example, CYP2J2 transgenic mice have a reduced rate of arrhythmia induction (Westphal et al, 2013). Our previous study also found that knockout of CYP2J3/ 10 in rats led to heart disease (Lu et al, 2020). In addition, CYP2J2*7 allele has been reported to be associated with stroke and CVD (Wang SY.…”
Section: Discussionmentioning
confidence: 92%
“…First, we used the PubMed database [ 75 ] and characterized each of the 39 novel PAG-related DEGs of the tame and aggressive rats ( Table 2 ) by answering the question as to how under- or overexpression of their human orthologs can aggravate or alleviate ARDs [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic mice with cardiac-specific CYP2J2 overexpression and subsequent elevated intracardiac EET levels, exhibit enhanced cardiac I Ca,L , K ATP , transient outward K + ( I to) currents, and shortened cardiac action potential duration without incidences of arrhythmogenesis or sudden cardiac death 44 . In parallel, cardiac-specific CYP2J3/10 −/− transgenic rats (rat isoforms of human CYP2J2) exhibited 75% loss in metabolic activity and 66.6% reduction in in vivo probe substrate clearance compared to WT rats 45 . Additionally, creatine kinase-muscle brain type, serum creatine kinase and their ratio were considerably increased indicative of myocardial injury and cardiomyocyte damage 46 .…”
Section: Discussionmentioning
confidence: 99%